2022
DOI: 10.1037/neu0000817
|View full text |Cite
|
Sign up to set email alerts
|

Does culture shape our understanding of others’ thoughts and emotions? An investigation across 12 countries.

Abstract: Measures of social cognition have now become central in neuropsychology, being essential for early and differential diagnoses, follow-up, and rehabilitation in a wide range of conditions. With the scientific world becoming increasingly interconnected, international neuropsychological and medical collaborations are burgeoning to tackle the global challenges that are mental health conditions. These initiatives commonly merge data across a diversity of populations and countries, while ignoring their specificity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 94 publications
1
19
0
Order By: Relevance
“…Numerous studies have found that males underperform females in ToM tasks. These reports obtain in both adults 54 – 62 and children 63 68 across dozens of languages and societies 69 , including a small-scale one (nomadic pastoralist 63 ). The available findings do not establish whether this gender difference is universal or inherent to biological sex 70 , 71 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that males underperform females in ToM tasks. These reports obtain in both adults 54 – 62 and children 63 68 across dozens of languages and societies 69 , including a small-scale one (nomadic pastoralist 63 ). The available findings do not establish whether this gender difference is universal or inherent to biological sex 70 , 71 .…”
Section: Introductionmentioning
confidence: 99%
“…Method bias indicates that nuisance arises due to inappropriate sampling, instrument design, and administration process. One example of administration bias is that miscommunication is almost certain to occur between testers and testees from different cultural backgrounds ( van de Vijver, 2002 ; Quesque et al, 2022 ). Item bias is possible when an item has different meanings across cultures ( Benítez et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The modernist psychologies of the Global North were the focus here because the analysis built on the methods of Friman and colleagues. However, by doing so, we neglected other approaches such as indigenous psychologies and the diversity of cultures (Alvarez et al, 2020; Arnett, 2008; Leong et al, 2017; Millner et al, 2021; Pickren, 2009; Quesque et al, 2022; Singer et al, 2021).…”
Section: Discussionmentioning
confidence: 99%